Estratégia de controle para a operação ilhada autônoma de uma unidade eólica de geração associada a banco de baterias - Dranka, Géremi Gilson (2014)
The insertion and expansion of distributed generation bring about intrinsic challenges, especially concerning to the reliability and operation of the electric power system, which results in a paradigm shift imposed on power distribution systems. Among the challenges and opportunities associated to distributed generation, the islanded operation of distribution systems and microgrids has grown considerably. In this context, this paper proposes operational and control strategies to properly allow the operation of a wind generation system. The proposed control is based on a supplementary control loop, added to the speed control loop of the wind turbine. The proposed control loop consists of a paradigm shift to control the DC-link voltage, since in traditional systems the DC-link voltage is usually controlled only by the BESS. The proposed supplementary control loop reduces the number and duration of the BESS actuations. Furthermore, the proposed strategy can contribute to enhance the reliability and the life cycle of the energy storage device. This work also proposes a new methodology for minimum sizing of battery energy storage systems to allow the islanded operation of wind power systems. The methodology considers a maximum load step to be supplied by the system. Finally, the proposed control and operational strategies with the BESS are evaluated and validated throughout mathematical analysis and simulation in the time domain using the proposed system. The proposed control strategy was effective in regulating the DC-link voltage, allowing the islanded operation of a wind power system based on synchronous generator with full-size power converters.